O Grande Mentecapto: romance carnavalizado - Castro, Maraiza Almeida Ruiz de [UNESP] (2014)
This study fulfills the aim of showing how the Brazilian novel O Grande Mentecapto: relato das aventuras e desventuras de Viramundo e de suas inenarráveis peregrinações, by Fernando Sabino, published in 1979, is a contemporary work which converses at the same time,with the carnivalized literary tradition. Based on Michael Bakhtin's considerations about carnivalization, is possible to note that the narrator of O Grande Mentecapto involves the read in a game of masks, changing his way to narrate modern and his text in ambivalent. Furthermore, polyphony and intertextuality, as well as Brazilian popular culture's elements, are present in the speeches that integrate the novel and help composing its multiplicity. The novel’s protagonist, Geraldo Viramundo, proves to be complex and ambivalent, taking on various identities and masks and bringing a typical liberating and renovating view of carnivalized works. Simultaneously, being a character that oscillates between hero and antihero, crazy and lucid, sublime and grotesque, free and trapped, familiar and unknown, marginalized and well liked, Brazilian and universal, he represents the big social conflicts and the human crisis in a deep manner. Finally, the Viramundo's trajectory is fragmented and contains the typical temporal and spatial imprecision of contemporary works while the narrative converges all the time the symbolism of the public square, which characterize the carnivalized works. So, O Grande Mentecapto can also be read as an allegory of a determined Brazilian social structure, thorough relations done between fiction and social historical facts that occurred not only in the narrative time, but in the publication’s epoch of the novel. Therefore, we note that O Grande Mentecapto’s place in Brazilian literary production is a novel that rescues carnivalized tradition's elements combining them with contemporary literature's aspects